The Effect of the Jigsaw Cooperative Learning Model and the Student’s Initial Mathematical Abilities and Its Effect on the Mathematical Representation Ability and Learning Motivation of Students in the PAB 10 Sampali Private Elementary School - Nurhamimah Rambe; Edi Syahputra; E. Elvis (BIRCU, 2020)
The Influence of Jigsaw Cooperative Learning Model on Mathematical Representation Ability and Student Learning Motivation at PAB 10 Sampali Private Elementary School. Thesis. Medan: UNIMED Postgraduate Program, 2020. This study aims to determine 1) the magnitude of the influence of the learning model on students' mathematical representation abilities and learning motivation; 2) the magnitude of the influence of early mathematical abilities on the ability of mathematical representation and student learning motivation; and 3) the interaction between the learning model and the initial mathematical ability of the mathematical representation ability and student learning motivation. The research was conducted in private SD PAB 10 Sampali with a sample of 2 classes with each class totaling 35 students. This research is a type of experimental research all with a 2 × 2 factorial design. The results showed that there is an effect of the learning model on the students 'mathematical representation ability, where the jigsaw cooperative learning model has a 9.1% higher effect on students' mathematical representation abilities than the expository learning model, there is an effect of initial mathematical ability on students 'mathematical representation abilities, where the high initial mathematical ability of students has an 11.5% higher effect on students' mathematical representation abilities compared to low initial mathematical abilities, there is no interaction between the learning model and the students 'mathematical initial ability to the students' mathematical representation ability.